Implementasi Prinsip Akuntabilitas Pada Good Corporate Governance Dalam Meningkatkan Kinerja Karyawan - Yusi Irensi Seppa; Andi Sadriani (Indonesian Journal of Taxation and Accounting, 2024)
The principle of accountability is used to define the mission, implementation, and responsibilities of a business organization so that business management can run well. Responsibility includes stating or fulfilling the duties and authorities of a person or organization to fulfill the obligations set by the company. The implementation of Good Corporate Governance (GCG) properly can make it easy for a company to achieve its goals and can provide benefits and welfare to all parties in the company. This study aims to find out more about the implementation of the principle of accountability in Good Corporate Governance in improving employee performance, especially at PT. Megahputra Sejahtera. This study uses a descriptive qualitative method with a literature study approach and describes the phenomena and facts that exist or occur in the research object. Data were obtained from the results of observations and interviews of industrial visits. The study was conducted at PT. Megahputra Sejahtera. The data sources used are primary data sources obtained from interviews and secondary data sources obtained indirectly through intermediary media/library sources that can be utilized in research. The data collection technique used is observation by conducting comprehensive observations and informal conversational interviews, which are interview techniques that take place spontaneously and freely. Based on the results of the study, it can be concluded that the implementation of the principle of accountability in Good Corporate Governance (GCG) in improving employee performance, especially at PT. Megahputra Sejahtera has been carried out well from all supporting aspects. PT. Megahputra Sejahtera has compiled an organizational structure with the aim of clarifying the duties and responsibilities of its employees. With the existence of an organizational structure, it can support the achievement of targets that have been set effectively and efficiently. Employee performance at PT. Megahputra Sejahtera is reflected in job satisfaction and work discipline so that the results are positive. The higher the satisfaction and discipline, the better the performance produced.